Universal Design for Learning: Is It Gaining Momentum in Irish Education? - Margaret Flood; Joanne Banks (MDPI AG, 2021)
Responding to student diversity has become a key policy priority in education systems around the world. In addition to international and national institutional policies, major changes are underway in instructional practices and pedagogy in many national contexts. Universal Design for Learning (UDL) has become a key pedagogical approach used in education systems which seek to promote inclusive and equitable education in response to student diversity. Despite Ireland's policy commitment to inclusive education, UDL has been traditionally focused on the higher education sector with little discussion about the role UDL can play at primary and second-level education to achieve inclusion. Furthermore, there has been no research to date on the extent to which education policy reforms are introducing part, or all, of the aspects of the UDL framework. The purpose of this paper is to examine the extent to which UDL is gaining momentum in Irish primary and second-level education through an analysis of curriculum policy. This paper examines the development and evolution of UDL in Irish education policy over the past decade by exploring the use of UDL in national educational curriculum frameworks. The paper highlights how UDL is slowly and implicitly emerging in education policy at a national level but suggests further momentum could be gained from its inclusion in Initial Teacher Education (ITE) and professional development programmes. By exploring the development of UDL within existing policy contexts, the paper argues for a more explicit commitment to UDL as part of ongoing curriculum reform at the primary level, the review of Senior Cycle, and Ireland's broader inclusive education agenda.